The Immigration Control of Foreign Citizens Applying for Stay Permit in The Indonesian Territory Based on Act Number 6 of 2011 Concerning Immigration (Case Study at Class I Immigration Office TPI Jember) - Basuki Kurniawan; Riza Safin Nabila; Sareef Tehtae (Advances in Humanities and Contemporary Studies, 2023)
The Law on Immigration is a guideline for coordinating every human being to create an orderly and conducive activity for foreigners living in Indonesia. Even though the formation of a regulation of Law Number 6 of 2011 concerning Immigration in an effort to control foreign nationals. It is undeniable to see that the implementation of existing regulations against foreigners is still not working effectively, with the increasing number of confirmed cases of foreigners who abuse their residence permits. So there are questions about the application being carried out as it should. The focus of the problems studied are: 1. How is Immigration control of foreign nationals applying for a residence permit in Indonesian territory based on Law Number 6 of 2011 at the TPI Jember Immigration Class I office? 2. What are the obstacles and immigration efforts in applying for a residence permit bagi Foreign Citizens in the working area of ​​the Class I Immigration office TPI Jember? 3. What are the immigration measures for foreign nationals who do not apply for a residence permit and overstay in the work area of ​​the TPI Jember Immigration Class I office? The research that has been used by researchers is using a qualitative empirical juridical approach, which is how the researcher describes it at the time of research. The researcher also seeks to thoroughly examine the substance of the regulations regarding immigration control of foreign nationals who apply for a residence permit and those who violate a residence permit. The location of the research was carried out at the TPI Jember Class I Immigration Office. In determining the information also uses purposive. Data collection techniques carried out by researchers are using interviews, observation, and documentation. Followed by data analysis using triangulation of sources and techniques performed. The research results obtained by researchers, immigration supervision of foreign nationals, which includes entry and exit of foreigners who apply for residence permits in Indonesian territory, then monitoring every activity carried out by foreigners while in Indonesian territory. If the immigration official finds a foreigner carrying out suspicious or suspect activities, as well as a foreigner who abuses his residence permit in Article 78 of Law Number 6 of 2011 concerning Immigration, he will be subject to administrative action and may also be subject to sanctions in the form of deportation and detention